Psychoanalytic Criticism on song Lyrics Cancer by My Chemical Romance - Surbakti, Dea Evelyn; Soethama, Putu Lirishati; Laksminy, Luh Putu; Malini, Ni Luh Nyoman Seri Malini (Smart Edu Center, 2024)
This research delves into the feelings experienced by the main character in the song